Desarrollo y medio ambiente. El rol de la bioética en un contexto de cambios ambientales globales - Castro Salvador, Sofía (2012)
Development and environment. Bioethics role in a framework of global environmental changesThe article intends to demonstrate how the dominant development model drives the planet to environmental unsustainable limits. Since the 1950s the development model has been led by economic growth without considering other dimensions as social or environmental. Maddison (2005) explains both production and population have been significantly increased in the last century; however, at the same time regional blocs’ gaps have augmented, persisting poverty levels and malnutrition in some countries.However, production and consumption levels have risen triggering an energetic and environmental crisis. These levels have become unsustainable and are driven the world to catastrophic scenarios. In this context, bioethics rises to give people’s guidance concerning personal, social and naturebehavior. Anyway, behavior changes should happen in the shortest term since this will shape the future of the planet and humanity